A case of tracheal bronchus associated with right aortic arch and partial anomalous pulmonary venous connection - Vehbı DOGAN; İlker Ertuğrul; Yasemin Taşcı Yıldız; Utku Arman Örün; Selmin Karademir (KARE Publishing, 2016)
Tracheal bronchus includes a variety of bronchial anomalies arising in the trachea or main bronchus and directed toward the upper-lobe territory. Reported incidence varies from 1-3% in the pediatric population. It is generally associated with other congenital malformations, including costovertebral anomalies, congenital airway and lung anomalies, vascular anomalies, and congenital heart defects. Presently described was the case of a 14-year-old female with tracheal right-upper-lobe bronchus, right aortic arch with mirror image, and abnormal left upper pulmonary venous return to innominate vein.